Optimization of Hybrid Machining of Nomex Honeycomb Structures: Effect of the CZ10 Tool and Ultrasonic Vibrations on the Cutting Process - Oussama Beldi; Tarik Zarrouk; Ahmed Abbadi; Mohammed Nouari; Jamal-Eddine Salhi; Mohammed Abbadi; Mohamed Barboucha (Machines)
Machining Nomex honeycomb composite structures is crucial for manufacturing components that meet stringent industry requirements. However, the complex characteristics of this material require specialized machining techniques to avoid defects, ensure optimal surface quality, and preserve the integrity of the cutting tool. Thus, hybrid ultrasonic-vibration-assisted machining (HUSVAM) technology, using a CZ10 combined cutting tool, was introduced to overcome these limitations. To this end, a 3D numerical model based on the finite element method, developed using Abaqus/Explicit 2017 software, allows us to simulate the interaction between the cutting tool and the thin walls of the structure to be machined. The objective of this study was to validate a numerical model through experimental tests while quantifying the impact of critical machining parameters, including the rotation speed and tilt angle, on process performance, in terms of surface finish, tool wear, cutting force components and chip size. The numerical results demonstrated that HUSVAM technology allows for a significant reduction in the cutting force components, with a decrease of between 12% and 35%. Furthermore, this technology improves cutting quality by limiting the deformation and tearing of cell walls, while extending tool life through a significant reduction in wear. These improvements thus contribute to a substantial optimization of the overall efficiency of the machining process.